Semiotic Analysis of the Image of a Chair - Teixeira, Julio Monteiro; Matos, Luana Marinho; Perassi, Richard (Estudos Semióticos, 2011)
This paper is based on Charles Sanders Peirce’s semiotic theory, where the sign is considered to be anything that represents another entity other than itself. The theory adopted in this paper is used to study and present part of the signiﬁcance proposed by the observation of Thonet’s chair image – model 209. The study analyzed the chair in its formal and material aspects which are recognized by visual observation of the object. The intention is to emphasize furniture design as a ﬁeld of interaction of visual values associated to shapes, which are presented here as signs or elements of signiﬁcation. Historical and contextual data are not considered at ﬁrst in this study, which more speciﬁcally describes the visual elements of the object. These elements are considered to be signs that take part on the conﬁguration of the object’s signiﬁcation within current cultural context. However, when compared to other manifestations, this signiﬁcation places the object in historical-evolutionary context of furniture. The shapes, materials and processes of structuring are historically referenced in other pieces, allowing for the comparison of the object’s appearance with other furniture pieces, which were produced at other times or places throughout history.